User Experience Analysis of Government Property: A Case Study of Bandung Class 1 Immigration Office - Widita, Raissa Aqiella; Alfakhri, Muhammad Habib; Rukmana, Hilman Fazri (International Journal of Environment, Architecture, and Societies, 2025)
Government properties, such as immigration offices, are critical public-facing institutions that shape citizens’ and non-citizens’ perceptions of state efficiency, accessibility, and legitimacy. Unlike other public facilities, immigration offices serve as key gateways for mobility, legal identity, and inclusion, making their quality, functionality, and accessibility particularly urgent in the context of increasing global migration and administrative demand. This study aims to evaluate the quality of public services at the Class I Immigration Office in Bandung City by focusing on user perceptions and experiences. Previous assessments have mostly emphasized physical and administrative aspects, often overlooking the user experience, which is essential for evaluating service quality holistically. This research adopts a qualitative method using a grounded theory approach and content analysis of 122 Google Review entries. Data analysis is conducted in four stages: decontextualization, recontextualization, categorization, and compilation, applying open coding techniques. The findings reveal patterns in user perceptions regarding comfort, accessibility, service efficiency, and the quality of human resources. This study contributes to the development of public properties that are more participatory, inclusive, and user-oriented. Moreover, it demonstrates the potential of utilizing user-generated content (UGC) as a digital data source to support adaptive and sustainable public facility management policies. The results underline the importance of incorporating digital feedback mechanisms in public service evaluations to better align with citizen expectations in the digital era.